Mutations in type II Golgi-localized proton pyrophosphatase AVP2;1/VHP2;1 affect pectic polysaccharide rhamnogalacturonan-II and alter root growth under low boron condition in Arabidopsis thaliana - Onuh, Amarachukwu Faith; Miwa, Kyoko (Frontiers in Plant Science, 2023)
The essential plant nutrient boron is required for the crosslinking of the pectin polysaccharide, rhamnogalacturonan II (RG-II). The synthesis of the pectic polysaccharides takes place in the Golgi apparatus, acidified by proton pumps. AVP2;1/VHP2;1 is a type II proton pyrophosphatase localized in the Golgi apparatus, which possesses proton pumping activity coupled with pyrophosphate hydrolysis. Its activity and expression patterns have been previously revealed but its role in plants remains unknown. The aim of the present work therefore was to explore the physiological role of AVP2;1 in Arabidopsis thaliana. In the screening of mutants under low boron, a mutant carrying a missense mutation in AVP2;1 was isolated. This mutant showed increased primary root growth under low boron conditions but no significant difference under normal boron condition compared to wild type plants. T-DNA insertion caused similar growth, suggesting that reduced function of AVP2;1 was responsible. Root cell observation revealed an increase in meristematic zone length, cell number in meristem and length of matured cell in avp2;1 mutants compared to wild type under low boron. Calcium concentration was reduced in mutant root cell wall under low boron. RG-II specific sugars also tended to be decreased in mutant root cell wall under low and normal boron conditions. These results suggest that changes in cell wall component by mutations in AVP2;1 may possibly explain the increased root length of mutants under low boron. This supports the idea that AVP2;1 plays a role in pH homoeostasis in Golgi apparatus for pectin synthesis.